Viability and germination of olive embryos subjected to different conditions of fruit storage - de Souza, Rafaeli Aparecida Vieira; Braga, Francyane Tavares; Neto, João Vieira; de Mendonça, Elisabeth Aparecida Furtado; de Azevedo, Patrícia Helena; Cançado, Geraldo Magela de Almeida (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of different storage conditions on the preservation of the viability and germination of olive zygotic embryos. A completely randomized block design was used, in a 4x2 factorial arrangement. Fruits of the cultivar Santa Catalina were subjected to different storage conditions – plastic bag in refrigerator at 4–5°C and 15% relative humidity (RH), dissector in refrigerator at 4–5°C and 12% RH, plastic bag at laboratory room at 27±1°C and 55% RH, dissector in laboratory room at 27±1°C and 30% RH –, and to storage periods of 30 and 120 days. In vitro germination and viability were evaluated by the tetrazolium test at 30 and 120 days of storage. The highest germination rate (91.66%) and viability (33.33%) were observed at 4–5°C and 12% RH at 30 days. This storage condition preserves olive fruits for longer time.